The Content of the Concept of War and its Artistic Interpretation in Uzbek Classical Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the concept of war and its artistic interpretation in Uzbek classical literature. Throughout the history of Uzbek literature, themes of war and conflict have been prominently featured. This article analyzes these themes from the perspectives of heroism, patriotism, tragedy, and the human cost of war. By exploring the creative legacy of key figures such as Amir Timur, Alisher Navoi, Babur, and other significant writers, the various portrayals and interpretations of war in their works are discussed. The article highlights how heroism and patriotism are celebrated, the tragedies and human costs are lamented, and how literary and artistic methods are employed to convey the essence and significance of war.